2010
DOI: 10.3844/ajeassp.2010.201.206
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Implementation of Truncated Multipliers Using Spartan-3AN, Virtex-4 and Virtex-5 FPGA Devices

Abstract: Problem statement: The development cost for Application Specific Integrated Circuits (ASICs) are high, algorithms should be verified and optimized before implementation. The Digital Signal Processing (DSP), image processing and multimedia requires extensive use of multiplication. The truncated multipliers can easily be implemented using Field Programmable Gate Array (FPGA) devices. Approach: This research presented the comparative study of Spartan-3AN, Virtex-4 and Virtex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Field Programmable Gate Arrays (FPGAs) are good choice for hardware realization but with limitations in design optimization. Furthermore, FPGA implementation is good for prototyping where, the aim is to predict the behavior of design in real world applications, there are many DSP systems reported in literature few of them are (Palaniappan and Zulkifli, 2007;Benhamid and Othman, 2009;Rais et al, 2010;Rais, 2010;Teymourzadeh et al, 2010). Application Specific Integrated Circuits (ASIC) is the most feasible technology to realize DSP algorithms and any other complex algorithm, without much limitations in optimizing the design.…”
Section: Introductionmentioning
confidence: 99%
“…Field Programmable Gate Arrays (FPGAs) are good choice for hardware realization but with limitations in design optimization. Furthermore, FPGA implementation is good for prototyping where, the aim is to predict the behavior of design in real world applications, there are many DSP systems reported in literature few of them are (Palaniappan and Zulkifli, 2007;Benhamid and Othman, 2009;Rais et al, 2010;Rais, 2010;Teymourzadeh et al, 2010). Application Specific Integrated Circuits (ASIC) is the most feasible technology to realize DSP algorithms and any other complex algorithm, without much limitations in optimizing the design.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research efforts have been reported for making low power multipliers Rais, 2009a;2009b;Rais, 2010a;2010b;Rais et al, 2010;Rais and Al Mijalli, 2011a;2011c).…”
Section: Introductionmentioning
confidence: 99%
“…This is more pronounced in digital signal processing (DSP) applications that constitute large number of multiplications. In the DSP computational complexity of algorithms has increased to such extent that they require fast and efficient parallel multipliers (Agostini et al, 2007;Gierenz et al, 2010;Kong et al, 2008;Zemva and Verderber, 2007;Rais, 2009a;2009b;Rais, 2010;Rais et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the Field Programmable Gate Arrays (FPGAs) have emerged as a platform of choice for efficient hardware implementation and an attractive alternative to Application Specific Integrated Circuits (ASICs) (Rais, 2009a;2009b;Rais, 2010;Rais et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation